GOVERNING RELIGION: Critics of Indonesia's Government Social Cohesion and Religious Harmony Policy - Tunggul Ganggas Danisworo (Universitas Padjadjaran, 2023)
The condition of freedom of religion/belief in Indonesia is in a position that has the potential to disrupt social cohesion and religious harmony. Those threats and challenges are triggered by the structural condition of state policy and cultural condition of society. This research aims to provide an overview of the condition of religious harmony in Indonesia and analyze the structural and cultural problems that affect the condition of religious harmony in Indonesia. In analyzing this article, the author uses the concept of governing religion and security community. The method used in this research is descriptive qualitative using a library research approach through collecting and analyzing materials related to the research. The results of this study indicate that there are structural and cultural problems in religious harmony in Indonesia. The government is trying to formulate policies to manage religious harmony to maintain social stability in society, but these efforts have not been maximized and tend to have a negative impact on socio-cultural relations between religious communities in Indonesia which tend to trigger conflicts between religious communities in Indonesia.